Experimental investigation of mechanical and morphological properties of flax fiber reinforced epoxy composites incorporating SiC and Al2O3. (2020) - Sathish, S.; Kumaresan, K.; Prabhu, L.; Gokulkumar, S.; Karthi, N.; Vigneshkumar, N.
Abstract: The present research work investigates the influence of SiC and Al2 O3 on the mechanical and morphological properties of flax dispersed epoxy composites. Composites were fabricated via compression moulding by adding ceramic fillers like SiC and Al2 O3 in different proportions for improving tensile, flexural and impact properties of flax fiber incorporated with ceramics filler epoxy composites. Scanning Electron Microscopy is performed to analyse the microstructure and modes of failure of the composites. A tensile strength of 44.56 MPa, flexural strength of 112.56 MPa and impact strength of 28.57 kJ/m 2 are the results for 20 wt% of flax fiber and 8 wt% of SiC and were the maximum values. The increase of SiC upto 8 wt% had a significant influence on the mechanical properties of the composites.